2008
DOI: 10.1097/aln.0b013e31818629db
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrous Oxide Anesthesia on Plasma Homocysteine and Endothelial Function

Abstract: Nitrous oxide-based anesthesia increased plasma homocysteine and significantly impaired endothelial function in patients undergoing noncardiac surgery. Nitrous oxide-based anesthesia could be a risk factor for postoperative cardiovascular morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 35 publications
4
52
1
Order By: Relevance
“…Desflurane appears to exert worse pulmonary vascular effects than isoflurane, probably through sympathetic activation [42,43]. Some studies suggest that nitrous oxide as a supplemental anaesthetic agent may increase PVR, especially in those with pre-existing elevated PVR [44], and it may also adversely influence endothelial function [45]. An increase in adverse cardiovascular events following its use in major surgery has been observed [46], possibly also through adverse pulmonary vascular effects of increased sympathomimetic stimulation [47,48] or hypoxia [49], and a study addressing these questions is ongoing [50].…”
Section: Discussionmentioning
confidence: 99%
“…Desflurane appears to exert worse pulmonary vascular effects than isoflurane, probably through sympathetic activation [42,43]. Some studies suggest that nitrous oxide as a supplemental anaesthetic agent may increase PVR, especially in those with pre-existing elevated PVR [44], and it may also adversely influence endothelial function [45]. An increase in adverse cardiovascular events following its use in major surgery has been observed [46], possibly also through adverse pulmonary vascular effects of increased sympathomimetic stimulation [47,48] or hypoxia [49], and a study addressing these questions is ongoing [50].…”
Section: Discussionmentioning
confidence: 99%
“…Whether this acute effect translates into clinical outcomes of relevance has been the research objective of two recent prospective randomized control trials in adults (4,6). In these trials, nitrous oxide-induced acute hyperhomocysteinemia (>13.4 µmol/L) was associated with increased risk of myocardial ischemia (6), and other major post-surgical complications (4).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence indicates that homocysteine acutely rises as a side effect of exposure to nitrous oxide during surgery in adults (1)(2)(3)(4)(5)(6)(7)(8)(9). Homocysteine is an intermediary metabolite in metabolism of the sulfurcontaining amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017 was an extensive study published which clearly demonstrated that postoperative adverse effects such as postoperative fever, wound infection, pneumonia, pulmonary atelectasis, and severe nausea or vomiting decreased when nitrous oxide was avoided [35]. Endothelial function was impaired after surgery in patients with cardiovascular disease, but seemingly only in those exposed to nitrous oxide [36]. The duration of nitrous oxide exposure strongly correlated with the extent of endothelial dysfunction.…”
Section: The Adverse Effects Of Nitrous Oxidementioning
confidence: 99%